Co-pyrolysis of empty fruit bunch and high-density polyethylene over HZSM-5 : Thermogravimetric, kinetic and thermodynamic analysis - Nadhilah Aqilah, Shahdan; Balasundram, Vekes; Shameli, Kamyar; Ali, Roshafima Rasit; Norazana, Ibrahim; Ruzinah, Isha (Scanditale AB, 2021)
This study conducted non-catalytic and catalytic co-pyrolysis of empty fruit bunch (EFB) and high-density polyethylene (HDPE) with HDPE-to-EFB mass ratios of 1:0, 0:1, and 1:1 via thermogravimetric analyser (TGA) and the application of Coats-Redfern method for kinetic and thermodynamic analysis. Hydrogen-exchanged zeolite socony mobil-5 (HZSM-5) catalyst was used with a catalyst-to-feedstock mass ratio of 1:1 for all the catalytic samples. From TGA results, the highest amount of volatilized matter in Phase II was obtained from non-catalytic pyrolysis of HDPE (NCP: 98.6 wt%) while the lowest amount of volatilized matter in Phase II was obtained from non-catalytic pyrolysis of EFB (NCB: 67.3 wt%). The activation energy for the pyrolysis of HDPE was highest followed by the co-pyrolysis of EFB and HDPE and pyrolysis of EFB, for both non-catalytic and catalytic runs. The activation energy based on the HDPE-to-EFB mass ratio was obtained in the following order: NCP (353.6 kJ/mol) > CP (214.3 kJ/mol) > NCPB (109.6 kJ/mol) > CPB (64.7 kJ/mol) > NCB (25.8 kJ/mol) > CB (24.4 kJ/mol). For thermodynamic analysis, ΔH and ΔG were positive for all the runs while ΔS, was negative for the non-catalytic and catalytic pyrolysis of EFB and co-pyrolysis of HDPE and EFB (NCB, NCPB, CB and CPB) and positive for the non-catalytic and catalytic pyrolysis of HDPE (NCP and CP).